An Evaluation of English Language Textbook for Senior High School Students in Indonesia - Mubarok, Husni; Sofiana, Nina; Mahendra, Danang (KnE Social Sciences, 2024)
The transition from the revised 2013 curriculum in Indonesia to the Merdeka curriculum necessitates the utilization of learning resources, particularly textbooks employed by teachers and students in teaching and learning process. Consequently, this study aims to evaluate English textbooks utilized for the tenth grade of senior high schools in Indonesia. This research employs a qualitative approach with a content analysis design. The subject of this research is an English textbook designed for the tenth grade at the high school level, focusing on on odd semester material. The analysis of the textbooks took into account aspects of content feasibility and presentation. The study’s findings indicate that, in terms of content feasibility: 1) three chapters scored below four on the compatibility of materials with learning objective indicator, 2) three chapters scored below four on the accuracy of the materials indicator, and 3) three chapters scored below four on the supporting materials indicator. In terms of presentation feasibility, some chapters some chapters still received a score of two on the presentation of the material indicator, particularly in the project-based learning sub-indicator. The study’s results suggest that curriculum changes should be accompanied by adjustments to the learning resources utilized by teachers and students. Keywords: English textbook, content analysis, senior high school